Sexualizing Power in Naturalism - Gammel, Irene (University of Calgary Press, 1994)
This book sheds light on the function of female sexuality in a predominantly male genre: naturalist fiction. Gammel reveals that naturalism is frequently implicated in the very power structures it critiques. Reading European and North American naturalism through the lens of feminist and Foucaultian theories of power, Gammel argues that twentieth-century naturalism increasingly deconstructs itself in its depiction of sexuality, inevitably exposing the genre's internal ideological contradictions. The book makes a special contribution to Canadian studies.